Tradisi Nyadran sebagai Praktik Sosio Ekologis dalam Relasi Antar Manusia, Budaya, dan Lingkungan di Kabupaten Trenggalek - Riris Dwi Ranti; Merlyn Dwi Marsella; A Zahid (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The Nyadran tradition at Dam Bagong in Ngantru Village, Trenggalek Regency, represents a form of local wisdom that functions not only as a cultural ritual but also as a socio-ecological practice connecting humans, culture, and the environment. This study aims to analyze the socio-ecological construction embedded in the Nyadran tradition and to explain how the tradition fosters environmental awareness and social solidarity within the local community. The research employs a qualitative approach using in-depth interviews, participant observation, and documentation as data collection techniques during the implementation of the Nyadran ritual. Informants were selected through purposive sampling, focusing on individuals with extensive knowledge of the history, meaning, and practices of the tradition. The findings reveal that Nyadran serves as a social mechanism for maintaining harmonious relationships between humans and nature through communal activities such as collective environmental cleaning, the buffalo head offering ritual, and the equitable distribution of ritual resources. The tradition also strengthens collective awareness regarding water resource conservation, environmental sustainability, and the fair use of natural resources. Furthermore, Nyadran reinforces cultural identity and social cohesion while functioning as a social infrastructure that supports ecological sustainability and community-based environmental risk mitigation through local wisdom.